Observations sur le phénomène d’upwelling au littoral roumain de la Mer Noire - Șerpoianu, Gheorghe (Cercetări Marine - Recherches Marines, 2026)
In the paper are presented the most characteristic situations of the upwelling recorded at the Romanian Black Sea coast. On this purpose the daily variations of the temperature and salinity of the sea water were analyzed, in correlation with the direction and speed of the wind.